ECONOMIC HARDSHIP AND INTENTION TO QUIT: A QUANTITATIVE STUDY OF SMALL BUSINESSES ENTERPRISES IN ENUGU STATE, NIGERIA - Onwubiko, Emmanuel (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The increasing economic hardship in Nigeria has presented various businesses with high levels of distress that might exacerbate the intention to exit the business. The primary purpose of the present paper was to examine the intention to quit a business based on economic hardship. Although much has been written on the challenges of SMEs in Nigeria, this study explored whether economic hardship can predict the intention to quit.